Commutators of Multilinear Singular Integrals on Weighted Herz Spaces. (23rd June 2015) - Wang, Baozhen; Wang, Huimin
Abstract : Supposeb → = ( b 1, …, b m ) ∈ ( B M O ) m, T Π b is the iterated commutator ofb → and them -linear Calderón-Zygmund operatorT . The purpose of this paper is to discuss the boundedness properties ofT Π b on weighted Herz spaces with general Muckenhoupt weights.